2017
DOI: 10.1016/j.compmedimag.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing deep convolutional neural network scheme for breast cancer diagnosis with unlabeled data

Abstract: In this study we developed a graph based semi-supervised learning (SSL) scheme using deep convolutional neural network (CNN) for breast cancer diagnosis. CNN usually needs a large amount of labeled data for training and fine tuning the parameters, and our proposed scheme only requires a small portion of labeled data in training set. Four modules were included in the diagnosis system: data weighing, feature selection, dividing co-training data labeling, and CNN. 3158 region of interests (ROIs) with each contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
110
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(120 citation statements)
references
References 27 publications
0
110
0
1
Order By: Relevance
“…Neural network based methods rely heavily on the support of big data. A semi-supervised algorithm has been proposed to deal with a large amount of unlabeled data with CNN approaches [167]. Their approaches using unlabeled data increased the overall accuracy, rather than just using labeled data.…”
Section: Computer Aided Diagnosismentioning
confidence: 99%
“…Neural network based methods rely heavily on the support of big data. A semi-supervised algorithm has been proposed to deal with a large amount of unlabeled data with CNN approaches [167]. Their approaches using unlabeled data increased the overall accuracy, rather than just using labeled data.…”
Section: Computer Aided Diagnosismentioning
confidence: 99%
“…In general, biopsy results can be used as benign/malignant labels. Unfortunately, most clinical samples generally do not have biopsy results . In clinical diagnosis, radiologists assign the breast ultrasound images a Breast Imaging, Reporting and Data System (BI‐RADS) rating, which expresses the malignancy probability of breast tumors, as displayed in Table .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most clinical samples generally do not have biopsy results. [17][18][19] In clinical diagnosis, radiologists assign the breast ultrasound images a Breast Imaging, Reporting and Data System (BI-RADS) rating, which expresses the malignancy probability of breast tumors, as displayed in Table I. However, in general, only samples with high BI-RADS ratings will be biopsied.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the diagnostic accuracy was 82.43%. A semi-supervised deep convolutional neural network [23] was developed for breast cancer diagnosis, which used large amount of unlabeled data to improve the accuracy. SVM, KNN, C4.5 and NB models have been implemented and tested on 699 samples for breast cancer detection [24].…”
Section: A Principal Component Analysis (Pca)-cross Entropy Optimizatmentioning
confidence: 99%
“…The Convolutional Neural Network (CNN) [23] model is inspired from ANN and was implemented and tested over 3,158 data samples. The CNN model is composed of neurons with substantial weight and bias can be learned.…”
Section: A Principal Component Analysis (Pca)-cross Entropy Optimizatmentioning
confidence: 99%